Examining Delayed Recall in Cochlear Implant Users Using the Montreal Cognitive Assessment, California Verbal Learning Test, Third Edition, and Item Specific Deficit Approach: Preliminary Results - Brumer, Nadav; Elkins, Elizabeth; Parada, Jennifer; Hillyer, Jake; Parbery-Clark, Alexandra (Frontiers in Psychology, 2021)
Purpose: Recent studies using the Montreal Cognitive Assessment (MoCA) suggest delayed recall is challenging for cochlear implant (CI) users. To better understand the underlying processes associated with delayed recall in CI users, we administered the MoCA and the California Verbal Learning Test, Third Edition (CVLT-3), which provides a more comprehensive assessment of delayed recall ability. Methods: The MoCA and CVLT-3 were administered to 18 high-performing CI users. For the CVLT-3, both the traditional scoring and a newer scoring method, the Item-Specific Deficit Approach, or ISDA, were employed. Results: The original MoCA score and MoCA delayed recall subtest score did not relate to performance on any CVLT-3 measures regardless of scoring metric applied (i.e. traditional or ISDA). Encoding performance for both the CVLT-3 and ISDA were related. Consolidation, which is only distinctly defined by the ISDA, related to CVLT-3 cued delay recall performance but not free delay recall performance. Lastly, ISDA retrieval only related to CVLT-3 measures when modified. Conclusion: Performance on the MoCA and CVLT-3 in a high performing CI patient population were not related. We demonstrate that the ISDA can be successfully applied to CI users for the quantification and characterization of delayed recall ability; however, future work addressing lower performing CI users, and comparing to normal hearing controls is needed to determine the extent of potential translational applications. Our work also indicates that a modified ISDA retrieval score may be beneficial for evaluating CI users although additional work addressing the clinical relevance of this is still needed.